Analisis Korespondensi Data Akreditasi Perguruan Tinggi di Lembaga Layanan Pendidikan Tinggi Wilayah 4 (LLDIKTI4) Jawa Barat dan Banten - Rifqi Naufaldi Putra Pratama; Marizsa Herlina (Bandung Conference Series: Statistics, 2024)
Abstract. Education is a key pillar of a nation's development. Well-managed education can produce high-quality resources. The role of LLDIKTI is to facilitate the enhancement of the quality of higher education, conduct evaluations, and report on the improvement efforts of universities within its region. Accreditation is an effort to ensure that universities meet the quality standards set by the government. The purpose of this study is to visually explore the relationship between the type of higher education institutions and the types of accreditation. This research employs correspondence analysis, a statistical technique used to explore the relationships between categorical variables. The data used in this study is the accreditation data of higher education institutions from June 2023. The categorical variables analyzed are the type of higher education institutions and the types of accreditation, presented in a contingency table format. This secondary data was obtained from performance reports released during the Practical Course of the Statistics Study Program, Faculty of Mathematics and Natural Sciences, at Universitas Islam Bandung, conducted at the Higher Education Service Institution Region 4 (LLDIKTI 4) in West Java and Banten. The results of the correspondence analysis on the accreditation data of higher education institutions at LLDIKTI 4 in West Java and Banten in June 2023 indicate a visual relationship between the type of higher education institution and the types of accreditation in the Higher Education Accreditation data from June 2023. Abstrak. Pendidikan merupakan pilar utama pembangunan suatu Negara. Pendidikan yang terkelola baik dapat menghasilkan sumber daya berkualitas. Tugas LLDIKTI adalah memfasilitasi peningkatan mutu penyelenggaraan pendidikan tinggi, pelaksanaan evaluasi dan pelaporan fasilitasi peningkatan mutu perguruan tinggi yang berada di wilayahnya. Akreditasi merupakan upaya untuk memastikan bahwa perguruan tinggi menerapkan standar mutu yang telah ditetapkan pemerintah. Tujuan penelitian ini untuk mengetahui keterkaitan secara visual antara bentuk perguruan tinggi dengan jenis Akreditasi. Penelitian ini menggunakan metode analisis korespondensi, sebuah teknik statistik yang digunakan untuk mengeksplorasi hubungan antara variabel kategorikal. Data yang digunakan dalam penelitian ini adalah data Akreditasi perguruan tinggi pada bulan Juni 2023, Variabel kategorikal yang dianalisis adalah variabel Bentuk Perguruan tinggi serta variabel Akreditasi yang disajikan dalam format tabel kontingensi. Data sekunder ini diperoleh dari laporan capaian yang dikeluarkan selama pelaksanaan Kuliah Praktik Prodi Statistika Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Islam Bandung di Lembaga Layanan Pendidikan Tinggi Wilayah 4 (LLDIKTI4) Jawa Barat dan Banten. Hasil analisis korespondensi pada data Akreditasi perguruan tinggi di Lembaga Layanan Pendidikan Tinggi Wilayah 4 (LLDIKTI4) Jawa Barat dan Banten pada bulan Juni Tahun 2023 menunjukkan adanya keterkaitan secara visual antara bentuk perguruan tinggi dengan jenis Akreditasi pada data Akreditasi Perguruan Tinggi bulan Juni Tahun 2023.